INDUCED MUTATION IN TRADITIONAL AROMATIC RICE – FREQUENCY AND SPECTRUM OF VIABLE MUTATIONS AND CHARACTERIZATIONS OF ECONOMIC VALUES - SATISH KR. CHAKRAVARTI; H. KUMAR; J. P. LAL; MANISH K. VISHWAKARMA (The Bioscan, 2012)
With a view to including viable mutations of economic importance in two traditional non–Basmati rice varieties, namely, Kala Namak and Badshah Bhog, dry seeds were treated with 10, 20, 30 and 40kR doses of gamma rays and EMS (0.2%), alone and in combination. Bulk seeds of M1 plants (showing pollen sterility greater than 40% or more) from each treatment were sown for generation advancement. Both frequency and spectrum of viable mutants and characterizations of economic importance varied with the treatment as well as genotypes. The treatment 40kR + EMS followed by 20kR + EMS in Kala Namak while EMS followed by 20kR + EMS and 40kR + EMS in Badshah Bhog were most desirable in including viable mutants; combination treatments were most effective. The genotypes Kala Namak was more sensitive than the Badshah Bhog with regard to the frequency of viable mutants. As regards to spectrum of viable mutations, a total of 15 types of macro- mutations were observed; 10 types in Kala Namak and 12 types in Badshah bhog. Out of 313 viable mutants in two genotypes, the frequency of different mutants over genotypes were 135 (semi-dwarf), 29(early maturing), 24(increased tillering), 9(bushy and stiff stem), 12(broad and narrow leaf), 4(pigmented node), 13(short slender grain), 38(straw colour grain), 11(change in grain size) and 29(high yielding). Isolation of few semi- dwarf mutant coupled with earliness have assumed great significance in improving traditional aromatic rice.